2021
DOI: 10.1177/21582440211056606
|View full text |Cite
|
Sign up to set email alerts
|

Why Do People Continue Using Fitness Wearables? The Effect of Interactivity and Gamification

Abstract: Technology use for personal health management should not only be assessed in terms of the rate of adoption but also examined in the form of sustained use to ensure the long-term benefit. This study addressed the issue of the continued use of wearable devices by ensuring value co-creation among a user, the wearable device, and other users within a service system. This study was a scenario-based experiment to examine interaction design, including interactivity level and game dynamics, which act as a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In our study population, around 60% of the patients were still actively using the device at the time of the interview, but the rest had stopped. Reasons for stopping varied, but a big factor could have been the lack of certain features that can improve useability and interest, like a high level of gamification or interactivity [ 20 ]. However, it is also important to note that around half of the patients who discontinued use continued healthy routines that they formed while still using the device.…”
Section: Discussionmentioning
confidence: 99%
“…In our study population, around 60% of the patients were still actively using the device at the time of the interview, but the rest had stopped. Reasons for stopping varied, but a big factor could have been the lack of certain features that can improve useability and interest, like a high level of gamification or interactivity [ 20 ]. However, it is also important to note that around half of the patients who discontinued use continued healthy routines that they formed while still using the device.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that AR-based applications could provide learners with various types of real-time information feedback, including visual and haptic feedback, in order to enhance their learning effectiveness (Belda-Medina & Calvo-Ferrer, 2022 ; Chiang et al, 2022 ; Jaszczur-Nowicki et al, 2021 ; Rodríguez et al, 2022 ; Wang et al, 2022 ; Yilmaz et al, 2022 ). Such timely and interactive feedback can help students better understand their learning goals, enhance their concentration and learning motivation, and arouse their interest or curiosity (Steele & Fullagar, 2009 ; Windasari & Lin, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Therefore, some challenges and skills are necessary for tasks or activities, resulting in an optimal learning experience in a virtual learning environment. Similarly, information feedback (i.e., feedforward, cognitive, outcome) is meaningful and valuable for learners, improving their flow state (i.e., concentration, a sense of control, and enjoyment) (Csíkszentmihályi, 1975 , 1990 ; Hattie & Timperley, 2007 ; Windasari & Lin, 2021 ). It can be inferred feedback is positively related to flow experience (e.g., Buil et al, 2018 ; Guo & Ro, 2008 ; Kajitani et al, 2020 ; Wang & Wang, 2008 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%